Impact of social isolation caused by the COVID-19 pandemic on the mood profile of active and sedentary older adults: physical activity as a protective factor - D'Oliveira A.* (2023)
Copyright © 2023 Andrade, D’Oliveira, dos Santos, Bastos, Corrado, Vilarino and Diotaiuti.Background: The COVID-19 pandemic has changed our habits and lifestyle due to social isolation and mobility restrictions. This new scenario, together with the fear of contracting the coronavirus, influenced mental health, especially among older adults, who presented reductions in social contact and physical activity (PA). Thus, the objective of the study was to analyze the impact caused by social isolation during the COVID-19 pandemic on the mood states of active and sedentary older adults. Methods: This is an observational study conducted during the COVID-19 pandemic. Older adults aged over 60 years, who were registered in the database of the Secretariat for the Promotion of Citizenship from a city in southern Brazil, participated in the research. An online questionnaire was applied with questions about sociodemographic characteristics, level of PA, confinement, and mood states in two periods: May 2020 and June 2021. The Mann–Whitney U test was used to compare the mood states of active and inactive individuals during the pandemic. Results: One hundred and fifty participants answered the questionnaire, of which 80 (53.3%) reported practicing PA. More active older adults suffered fewer changes in mood when compared to inactive older adults, with lower levels of confusion (p = 0.035), depression (p = 0.002), and fatigue (p = 0.000). Older adults confined for more than 50 days were more likely to develop depression. In addition, the mood state correlated with the variable fear of contracting the coronavirus; the greater the fear, the greater the mental confusion, depression, fatigue, and tension, and the lower the vigor in the older adults. The practice of PA is also correlated with the mood state; the greater the number of hours dedicated to PA, the lower the confusion, depression, fatigue, and tension of the older adults. Conclusion: The practice of PA positively influenced the mental health of older adults during periods of isolation and social restrictions. PA has a protective factor for the development of mental health problems and improves mood states, with greater time performing PA leading to more benefits.